1996
DOI: 10.1136/hrt.76.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness in young patients with familial hypercholesterolaemia.

Abstract: Objective-To assess the extent of early atherosclerotic changes of the carotid arteries in young patients with familial hypercholesterolaemia (FH) detected as increased intima-media thickness (IMT), and to determine the relations between IMT and some clinical and blood variables such as lipid and lipoprotein(a) (Lp(a)) concentration and haemostatic factors. Design-The IMT of the carotid bifurcation, the proximal 1 cm of the internal carotid artery, and the distal 1 cm of the common carotid artery was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 26 publications
2
47
1
Order By: Relevance
“…Consistent with these observations are the rarity of cases of premature CHD in patients with Tangier Disease or LCAT deficiency (21) when other traditional risk factors are lacking and the low likelihood of CHD in the setting of normocholesterolemic low HDL-C (22). This is in contrast to hyperlipidemic states (e.g., familial hypercholesterolemia) where increased cIMT has been consistently observed (23)(24)(25). Thus, while our data do not preclude the importance of low HDL-C (or its associated genetic variants) in augmenting CHD risk, they temper these suggestions and raise the possibility that the genetic mutations causing low HDL-C as reported herein, may be insufficient to cause appreciable carotid atherosclerosis as assessed by β-mode ultrasound imaging.…”
Section: Discussionmentioning
confidence: 47%
“…Consistent with these observations are the rarity of cases of premature CHD in patients with Tangier Disease or LCAT deficiency (21) when other traditional risk factors are lacking and the low likelihood of CHD in the setting of normocholesterolemic low HDL-C (22). This is in contrast to hyperlipidemic states (e.g., familial hypercholesterolemia) where increased cIMT has been consistently observed (23)(24)(25). Thus, while our data do not preclude the importance of low HDL-C (or its associated genetic variants) in augmenting CHD risk, they temper these suggestions and raise the possibility that the genetic mutations causing low HDL-C as reported herein, may be insufficient to cause appreciable carotid atherosclerosis as assessed by β-mode ultrasound imaging.…”
Section: Discussionmentioning
confidence: 47%
“…Cardiovascular disease (CVD) was more frequent in ESRD patients on hemodialysis and in FH than in controls, but the number of CVD events may not fully reflect the severity of the atherosclerotic disease in the patients. Using B-mode ultrasound, a technique that visualizes atherosclerotic changes in the walls of arteries, it has been demonstrated that carotid artery intima-media thickness is markedly increased, plaque is more frequent, and calcified plaque is common in FH and in ESRD (Haraki et al, 2001;Lavrencic et al, 1996;Pannier et al, 2000;Savage et al, 1998;Smilde et al, 1998;Tonstad et al, 1998). Thus, atherosclerotic disease is underestimated in FH and in ESRD if presented as CVD events only.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, high cholesterol in children has a substantial subclinical impact, which is already measurable from the age of 5 years. In children with a mutation, endothelial dysfunction can be observed (measured by the dilatation of the brachial artery associated with an intense post-ischaemic flow of arterial blood) [4], as well as a greater IMT thickening detected by carotid echography [5][6][7]. Secondly, high cholesterol levels in childhood increasingly appear to be a good predictor of cardiovascular risk later in life [8,9].…”
Section: Introductionmentioning
confidence: 99%